2000
DOI: 10.1095/biolreprod62.5.1297
|View full text |Cite
|
Sign up to set email alerts
|

A Premature Increase in Circulating Cortisol Suppresses Expression of 11β Hydroxysteroid Dehydrogenase Type 2 Messenger Ribonucleic Acid in the Adrenal of the Fetal Sheep1

Abstract: We have investigated the effect of intrafetal cortisol administration, before the normal prepartum cortisol surge, on the expression of 11beta hydroxysteroid dehydrogenase (11betaHSD) type 2 mRNA in the fetal adrenal. We also determined whether increased fetal cortisol concentrations can stimulate growth of the fetal adrenal gland or increase expression of adrenal steroidogenic enzymes. Cortisol (hydrocortisone succinate: 2.0-3.0 mg in 4.4 ml/24 h) was infused into fetal sheep between 109 and 116 days of gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Cortisol, therefore, appears to suppress 11 -HSD2 activity in the ovine placenta during late gestation. A similar inhibitory effect of fetal cortisol on 11 -HSD2 gene expression has been observed in adrenal glands of fetal sheep close to term (Ross et al 2000). The inverse correlation observed in the present study between plasma fetal cortisol and placental 11 -HSD2 activity also indicates that fetal cortisol is a physiological regulator of the placental conversion of cortisol to cortisone and suggests that it may increase placental exposure to bioactive glucocorticoids during late gestation.…”
Section: Discussionsupporting
confidence: 87%
“…Cortisol, therefore, appears to suppress 11 -HSD2 activity in the ovine placenta during late gestation. A similar inhibitory effect of fetal cortisol on 11 -HSD2 gene expression has been observed in adrenal glands of fetal sheep close to term (Ross et al 2000). The inverse correlation observed in the present study between plasma fetal cortisol and placental 11 -HSD2 activity also indicates that fetal cortisol is a physiological regulator of the placental conversion of cortisol to cortisone and suggests that it may increase placental exposure to bioactive glucocorticoids during late gestation.…”
Section: Discussionsupporting
confidence: 87%
“…While adrenal Hsd11b2 expression has been noted previously in the rat (Smith et al 1997) and other species (Yang & Matthews 1995, Ross et al 2000, its physiological significance remains uncertain. The HSD11B2 enzyme catalyzes the conversion of corticosterone to its biologically inert, 11-keto derivative 11-dehydrocorticosterone (11-DHC), and Yang & Matthews (1995) suggested that adrenal HSD11B2 may serve to limit exposure of adrenocortical cells to very high levels of corticosterone and/or provide a source of 11-DHC for reactivation within target tissues by HSD11B1.…”
Section: Discussionmentioning
confidence: 89%
“…Vascular catheters were implanted in the jugular vein of the ewe, a carotid artery, and jugular vein of the fetus, and in the amniotic cavity as previously described (Ross et al. ; Muhlhausler et al. ).…”
Section: Methodsmentioning
confidence: 99%